An Assessment of Administrative Law and Governance System in Nigeria - Oikhala, Gabriel Izokpu (NIU Journal of Social Sciences, 2020)
The stance of administrative law is to keep the powers of public administration within legal framework; protect the citizens against abuse of powers; and promote good governance. However, a cursory look at the present status of governance in Nigeria showed that many public administrators often breached administrative law. This trend has led to an increase in governance crisis with the flurry of insecurity, hardship and other socio-economic encumbrances in Nigeria. This paper assessed the stance of administrative law on governance system in Nigeria with a view to determining the state of governance in the country. Data were sourced from relevant textbooks, journals, newspapers, and other publications. The data obtained was analysed through descriptive method. Adopting the legal approach as theoretical framework, governance is identified as the primary function of government; public administration implements government policies, programmes, and projects on all governance issues; and administrative law is the government valid instrument for keeping the powers, and actions of public administration under legal bounds. The paper found the stance of administrative law as very supportive to governance system in Nigeria. It argued among others that the environment created by the present political system in the country was unsuitable for utilisation of administrative law on governance issues; leaving in an epileptic state. The paper suggested that government leadership and followership should undergo a rebranding exercise for a positive change in order to maintain a political system, which will encourage the application of administrative law to thrive towards issues of governance in Nigeria. Keywords: Law of Public Administration, Government and Governance, Separation of Powers, Rule of Law, Control of Administration